2016
DOI: 10.1111/hae.12893
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and pharmacokinetics of a new high‐purity factor X concentrate in subjects with hereditary factor X deficiency

Abstract: These results demonstrate that a dose of 25 IU kg(-1) pdFX is safe and efficacious for on-demand treatment and short-term prophylaxis in subjects with moderate or severe hereditary FX deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(92 citation statements)
references
References 12 publications
5
87
0
Order By: Relevance
“…Of the 3 bleeds that were assessed for efficacy, pdFX treatment efficacy was rated as excellent. These results are consistent with a previous study conducted in subjects aged ≥12 years in which pdFX successfully treated bleeds in 97% of subjects, and 83% of bleeds were treated with a single infusion …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Of the 3 bleeds that were assessed for efficacy, pdFX treatment efficacy was rated as excellent. These results are consistent with a previous study conducted in subjects aged ≥12 years in which pdFX successfully treated bleeds in 97% of subjects, and 83% of bleeds were treated with a single infusion …”
Section: Discussionsupporting
confidence: 93%
“…During extended prophylactic use of pdFX in subjects who had previously received treatment with other clotting factors—including 3 subjects who had received pdFX for compassionate use prior to study entry—no evidence was seen in this study population for the development of FX inhibitors. These data are consistent with previous pdFX studies in patients ≥12 years old with moderate to severe FXD, who also showed no sign of inhibitor development . In addition, no cases of FX inhibitor development have been reported in postmarketing safety surveillance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In summary, the PK characteristics of pdFX presented here are consistent with other coagulation factors used as replacement therapy in inherited bleeding disorders and are consistent with the observed haemostatic efficacy of the product in subjects aged ≥12 years with hereditary FX deficiency [14]. In addition, the 30-h t ½ of pdFX may facilitate a once-or twice-weekly prophylactic dosing schedule, depending on the required trough FX:C level.…”
Section: Study Populationsupporting
confidence: 80%
“…FX levels should be monitored to ensure therapeutic levels of 0.4 IU/mL have been achieved at the time of delivery (level C recommendation). PCC 20‐40 IU/kg (or factor X concentrate if available) to achieve factor X activity more than 0.4 IU/mL, further doses of PCC 10‐20 IU/kg once daily to maintain factor X activity more than 0.3 IU/mL for at least 3 days . Tranexamic acid 1 g 6 hourly is also recommended till the lochial loss is very light.…”
Section: Discussionmentioning
confidence: 99%